(untitled) (LEARNing Landscapes, 2014)
This article discusses the importance of teacher candidates writing poetry in their education methods classes in order to reflect upon and examine their beliefs about teaching and learning. Writing poetry in a teacher education context is also important because it prepares teachers to use these techniques with their own students. By writing poetry in the context of academic study, learners can see metaphorical connections between events and ideas. This stands in contrast to the idea put forth in the Common Core Standards that college and career readiness is best developed through reading and writing informational and argumentative texts.